Proteomic and functional analysis of alpaca (Vicugna pacos) sperm quality following in vitro capacitation with follicular and oviductal fluids - Torres Hualla, Edith A.; Martiarena, Alba; Buglio Ballesteros, María Gabriela; Medina Rojas, Maribel Fortunata; Rivera Chino, Cristian; Gandarillas Espezua, Daniel; Argañaraz, Martin E. (Frontiers in Veterinary Science, 2025)
Assisted reproductive technologies, such as in vitro fertilization, remain inefficient in camelids, largely due to gaps in understanding the molecular interactions that regulate sperm capacitation. Fertilization requires not only viable spermatozoa but also the precise modulation of capacitation by the peri-ovulatory microenvironment, including follicular fluid (FF) and oviductal fluid (OF). In this study, spermatozoa were incubated in Fert-TALP medium supplemented with FF or OF, and both functional outcomes and proteomic remodeling were assessed. Sperm treatments were evaluated in five independent biological replicates per individual (three individuals), with triplicate proteomics performed. FF (n = 20) was collected from pre-ovulatory follicles (7–9 mm) and OF (n = 10) from the corresponding ipsilateral oviducts, thereby reflecting the in vivo environment encountered by sperm in the female reproductive tract following mating. Incubation with FF enhanced progressive motility by 72%, rapid progressive motility by 169%, viability by 30%, and acrosome responsiveness by 30%, and was associated with a proteomic shift involving ~12% of proteins (p < 0.05). These included factors implicated in zona pellucida binding (LYPD4, PGK1, ANXA2, and TCP1 complex members) and galactose metabolism (MAOA, AKR1B1, GLA, and HK1). The enriched processes included glycolysis/gluconeogenesis, cytoskeletal reorganization, and protein maturation, all consistent with sperm capacitation. By contrast, sperm incubated with OF showed an underrepresentation of capacitation-related pathways, including the proteasome complex, sperm fibrous sheath, and TCA cycle. Moreover, the OF proteome (r = 2) revealed decapacitation-associated factors such as PEBP1 and PAFAH1B3, which likely stabilize membranes and delay premature capacitation. Together, these findings demonstrate complementary yet contrasting roles of FF and OF in modulating sperm physiology: FF acting as a capacitating medium, and OF providing a stabilizing environment. This study presents the first partial proteome of capacitated alpaca sperm together with matched reproductive fluids, providing mechanistic insights with direct implications for improving assisted reproduction in camelids.